Impact-induced deformation and ignition related to localized viscous shear flow heating for high-ductility composite energetic materials - Kun Yang; Hongzheng Duan; Yanqing Wu; Xiao Hou; Fenglei Huang (Materials & Design, 2022)
Understanding the impact-induced deformation and ignition properties of high-ductility composite energetic material (CEM), including high-energy propellants and casted high explosives, is fundamental to the safety design and usage of rockets and warheads and has been a broad concern in the fields of aerospace and defence. In this study, an impact ignition experiment is designed using a Split Hopkinson Pressure Bar to quantitate the continuum deformation and reaction responses of a high-ductility CEM sample undergone periodic impact loading pulses. The relation between macroscopic shear deformation rate and localized viscous shear flow heating, melting, and reaction is further investigated utilizing a macro-mesoscopic thermomechanical model. The results show that CEM sample is severely crushed to 2% of the original thickness and laterally extruded with a high shear rate (∼105 s−1). High shear deformation rate contributes to the localized viscous shear flow heating, thereby inducing temperature rise spike (∼200 K) and following ignition. Ignition of CEM sample occurs in the third compression pulse because the thinner sample exhibits a high velocity gradient, which causes a high viscous shear flow heating rate.